DOENÇA DE MACHADO JOSEPH: UM RELATO DE EXPERIÊNCIA - Scarton, Juliane; Gomes, Joseila S.; Kolankiewicz, Adriane C. B.; Rosanelli, Cleci L. S. P.; Ceratti, Jaqueline O.; Loro, Marli M. (Salão do Conhecimento, 2013)
Resumo